2014
DOI: 10.1016/j.redox.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylfumarate attenuates restenosis after acute vascular injury by cell-specific and Nrf2-dependent mechanisms

Abstract: Excessive proliferation of vascular smooth muscle cells (VSMCs) and incomplete re-endothelialization is a major clinical problem limiting the long-term efficacy of percutaneous coronary angioplasty. We tested if dimethylfumarate (DMF), an anti-psoriasis drug, could inhibit abnormal vascular remodeling via NF−E2-related factor 2 (Nrf2)-NAD(P)H quinone oxidoreductase 1 (NQO1) activity. DMF significantly attenuated neointimal hyperplasia induced by balloon injury in rat carotid arteries via suppression of the G1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 30 publications
(32 reference statements)
4
39
0
Order By: Relevance
“…248 Application of DMF can confer neuroprotection, reduce macrophage inflammation, and increase IL-10 production in mouse models of chronic experimental autoimmune encephalomyelitis. 253, 255 DMF also reduced intimal hyperplasia in a model of vascular injury, in an Nrf2-dependent mechanism involving upregulation of p21 Cip1 256 . The effects of Nrf2-inducing compounds such as DMF are not necessarily specific for HO-1, as Nrf2 regulates multiple effector enzymes.…”
Section: Therapeutic Stategies Involving Ho-1 Modulationmentioning
confidence: 84%
“…248 Application of DMF can confer neuroprotection, reduce macrophage inflammation, and increase IL-10 production in mouse models of chronic experimental autoimmune encephalomyelitis. 253, 255 DMF also reduced intimal hyperplasia in a model of vascular injury, in an Nrf2-dependent mechanism involving upregulation of p21 Cip1 256 . The effects of Nrf2-inducing compounds such as DMF are not necessarily specific for HO-1, as Nrf2 regulates multiple effector enzymes.…”
Section: Therapeutic Stategies Involving Ho-1 Modulationmentioning
confidence: 84%
“…Nrf2 activators have been shown to exhibit anti-proliferative effects in vitro and in vivo , in part, through Nrf2-mediated upregulation of HO-1 [5054]. To determine whether SFN-induced Nrf2/HO-1 and/or mTOR signaling contribute to inhibition of PDGF receptor signaling, VSMCs were subjected to target-specific downregulation of Nrf2 using specific siRNA.…”
Section: Resultsmentioning
confidence: 99%
“…However, under these conditions, SFN-mediated inhibition of PDGF-induced cyclin D1 expression and key proliferative signaling remains essentially the same, suggesting that SFN-mediated Nrf2 activation does not play an intermediary role toward suppressing PDGF-induced VSMC proliferation. At this juncture, it is important to note that pharmacological agents such as curcumin, trans-resveratrol, sulfasalazine (anti-inflammatory/immune-modulatory agent), and dimethylfumarate (an anti-psoriasis drug) inhibit VSMC proliferation in vitro and in vivo presumably through Nrf2-mediated upregulation of HO-1, as reported in recent studies [5054]. However, none of these studies has utilized Nrf2 gene-silencing strategy to support an obligatory role of Nrf2 activation toward inhibition of VSMC proliferation.…”
Section: Discussionmentioning
confidence: 96%
“…They also found that DMF protected endothelial cells from TNFα-induced apoptosis and the dysfunction characterized by decreased eNOS expression. In both cases, Nrf2 expression was dispensable since BG-12 failed to prevent both TNFα-induced cell apoptosis and decreased eNOS expression under siRNA knock-down of Nrf2 [77]. They concluded that BG-12 prevented abnormal proliferation in VSMCs and had a beneficial effect on TNFα-induced apoptosis and dysfunction in endothelial cells, both beneficial effects are Nrf2-dependent [77], as summarized in Fig.…”
Section: Dimethyl Fumarate and Its Potential For Preventing Diabetic mentioning
confidence: 96%
“…2. Schematic summary for the DMF protects TNF-α induced cell apoptosis mediated by Nrf2-NQO1 activity in human aortic cells (HAECs), reported by Oh et al [77].…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%